Analisis Jumlah Kendaraan Bermotor Dari Kegiatan Transportasi Di Wilayah Pengembangan – IV Kota Pekanbaru - Ayu Putri Permata MS; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The number of vehicles is very influential on the CO2 produced and can cause increased Greenhouse Gas emissions because it has the ability to absorb CO2 emissions. Pekanbaru Development Area IV is one of the Development Areas that has the potential to produce carbon dioxide (CO2) emissions. This research was conducted to determine the number of motorized vehicles and the value of CO2 emissions produced each day. The method used is recording traffic activities to calculate the amount of CO2 emissions. The research results obtained, namely the number of vehicles from transportation in the Development Area IV Pekanbarun can be concluded that the number of densest vehicles occurs on arterial roads on Sundays with the number of vehicles as much as 33,082 vehicles / day, for the collector road the highest number of vehicles on the Bukit Barisan road on Sundays as many as 19,186 vehicles / day, while for the densest local roads on the road I Work on Monday as many as 9,981 vehicles / day. Keywords: Greenhouse Gases, CO2 Emissions, Pekanbaru IV Development Area